Implementation of Balanced Scorecard as a Performance Measurement Tool in Bridging Strategy with Implementation at PT PLN (Persero) Bukittinggi Generation Implementation Unit - Ikhlas A, Muhammad; Yulihasri, Yulihasri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
PT. PLN Bukittinggi Generating Unit has a way to increase service productivity with Organizational Performance Value, Organizational Performance Value is the evaluation of real work results with quality and quantity standards produced by PT. PLN UP Bukittinggi. Basics of assessment using Key Performance Indicator, from six perspectives used as a measurement tool to assess the performance of PT. PLN UP Bukittinggi the author found that the customer perspective is not a priority in the Organizational Performance Value of PT. PLN UP Bukittinggi. In contrast to the concept of the Balanced Scorecard, the use of the Balanced Scorecard concept was found to be effective in knowing the underlying problems that exist and identifying opportunities for improvement. PT. PLN UP Bukittinggi has not implemented performance measurement using the Balanced Scorecard, but the writer wants to do research on the performance measurement system at PT. PLN UP Bukittinggi if using the Balanced Scorecard whether an increase or decrease in performance. Problems that are the object of research include: (1) the application of the Balanced Scorecard model is able to measure the performance of PT. PLN Bukittinggi Generation Unit correctly and accurately, (2) steps that must be taken in achieving the strategic targets set, (3) the application of the Balanced Scorecard in PT. PLN Bukittinggi Generating Unit in line with the Company's Vision and Mission. The method used in this research is descriptive exploratory research through a case study approach, the type of data used is primary data is data obtained through field research and secondary data, existing data and obtained from other sources that are still related to the research object collected directly or indirectly.